Recurrent stroke in a patient of lung cancer without pulmonary mass: A case report. Issue 5 (February 2018) - Wang, Lisha; Xu, Yan; Tuo, Minghui; Zhang, Lei; Zhang, Hong; Wang, Jing
Abstract: Rationale: Repeated occurring stroke in short intervals with hypercoagulability is unusual so in such cases the conventional vascular risk factors might not be the causes of stroke. Patient concerns: We have presented a case of 60-year-old male presenting with recurrent stroke due to thrombophilia. Diagnoses: Lung cancer was detected by superficial lymph nodes ultrasound and further pathological examination. Interventions: The patient suffered a recurrent stroke and he had persistently high level of D-dimer which suggested the diagnosis of thrombophilia, thus, he was treated with low-molecular-weight heparin. Unfortunately, the treatment was not effective for the patient and he died before any other treatments could be administered. Outcomes: Despite anticoagulant therapy, the patient suffered multiple episodes of stroke and ultimately died. Lessons: This case of recurrent stroke with coagulation disorders without evidence of cancer in imaging and blood test is rare. So in a stroke patient, we should consider malignancy or metastasis as a differential diagnosis as it may be the first manifestation of active cancer elsewhere.